From Subprime Loans to Subprime Growth? : Evidence for the Euro Area - Cihak, Martin; Koeva Brooks, Petya (Washington, D.C. : International Monetary Fund, 2009)
The global financial crisis has highlighted the potential of financial conditions for influencing real economic activity. We examine the linkages between the financial and real sectors in the euro area, finding that (i) bank loan supply responds negatively to declines in bank soundness; (ii) a cutback in bank loan supply has a negative impact on economic activity; (iii) a positive shock to the corporate bond spread lowers industrial output; and (iv) risk indicators for the banking, corporate, and public sectors show an improvement beginning in 2002-03, followed by a major deterioration since 2007. These estimates imply that the currently estimated bank losses would subtract some 2 percentage points from the euro area output (but with considerable uncertainty around the estimates).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet